Why social policy needs subjective indicators - Ruut Veenhoven (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2001)
There are many qualms about subjective indicators, and some people believe that social policy should better not use them. This paper consists of a review of these objections. It is argued that policy makers need subjective indicators for the following reasons: 1. Social policy is never limited to merely material matters; it is also aimed at matters of mentality. These substantially subjective goals require subjective indicators. 2. Progress in material goals can not always be measured objectively. Subjective measurement often is better. 3. Inclusive measurement is problematic with objective substance. Current sum scores make little sense. Using subjective satisfaction better indicates comprehensive quality of life. 4. Objective indicators do little to inform policy makers about public preferences. Since the political process also does not reflect public preferences too well, policy makers need additional information from opinion polls. 5. Policy makers have to distinguish between `wants' and `needs'. Needs are not observable as such, but their gratification materialises in the length and happiness of peoples' lives. This final output criterion requires assessment of subjective appreciation of life as a whole.
Keywords: 300; Sozialpolitik; Sozialer Indikator; Theorie; Meinung